Constitutional-economic regulation of property (Journal of actual problems of jurisprudence, 2022)
Constitutional economics, as a category, is insufficiently covered in the literature. In view of this, it is necessary to theoretically consider the essence of constitutional economics in the aspect of the relationship with law and economic efficiency. In addition, in order to form a clearer understanding of the constitutional economy, it is important to consider economic normativity. In this case, it is worth pointing out that the normativity of legislation and the normativity of economic and labor law are strongly interrelated. Economic normativity is a process in which legal norms will increasingly be subjected to compliance with the economic efficiency or rationality of trade.Property is the foundation of any economy. The nature of the economic system depends on how the constitutional and legal regulation of property issues is carried out. Moreover, the procedure for such regulation often significantly affects the political, social, demographic and other spheres of society. We can say that the constitutional and economic regulation of property issues is one of the most key moments in the regulation of society in general.Keywords: constitution, economics, regulation